2021
DOI: 10.1002/jbio.202100272
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Fourier ptychographic diffraction tomography with sparse annular LED illuminations

Abstract: Fourier ptychographic diffraction tomography (FPDT) is a recently developed label‐free computational microscopy technique that retrieves high‐resolution and large‐field three‐dimensional (3D) tomograms by synthesizing a set of low‐resolution intensity images obtained with a low numerical aperture (NA) objective. However, in order to ensure sufficient overlap of Ewald spheres in 3D Fourier space, conventional FPDT requires thousands of intensity measurements and consumes a significant amount of time for stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The adopted annular matched illumination configuration could provide a reliable and efficient approach for aberration correction on the transparent biospecimen. Moreover, as an extension to FPM, the technology of 3D FPM [68][69][70][71] is developed to further reveal the 3D phase information for thick samples. The existence of aberrations could also affect the imaging performance of the 3D phase imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The adopted annular matched illumination configuration could provide a reliable and efficient approach for aberration correction on the transparent biospecimen. Moreover, as an extension to FPM, the technology of 3D FPM [68][69][70][71] is developed to further reveal the 3D phase information for thick samples. The existence of aberrations could also affect the imaging performance of the 3D phase imaging.…”
Section: Discussionmentioning
confidence: 99%
“…As a light source, an annular LED array (central wavelength λ = 520 nm, 1586, Adafruit, USA) was used for the annular plane wave illuminations at various azimuthal angles. Recently, several researchers have shown that annular illuminations with the incident angle matching the objective NA (𝑁𝐴 𝑜𝑏𝑗 ) is the optimal condition for tomographic imaging 13,[62][63][64] . This illumination scheme optimally encodes both low-and high-spatial frequency information across the entire 3D volume using a small number of intensity measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Fourier ptychography imaging draws on the idea of synthetic aperture [1] , using LED arrays of different positions for imaging. Acquiring multiple low-resolution images containing different spectrum components, Fourier ptychography use the phase recovery technology, and finally obtains a high-resolution, large field of view imaging results [2][3][4][5][6][7][8] . The phase recovery process is essentially an inverse problem solved optimally.…”
Section: Introductionmentioning
confidence: 99%